Organophotocatalytic Aerobic Oxygenation of Phenols in a Visible‐Light Continuous‐Flow Photoreactor. Issue 38 (19th May 2021) - Wellauer, Joël; Miladinov, Dragan; Buchholz, Thomas; Schütz, Jan; Stemmler, René T.; Medlock, Jonathan A.; Bonrath, Werner; Sparr, Christof
Abstract: A mild photocatalytic phenol oxygenation enabled by a continuous‐flow photoreactor using visible light and pressurized air is described herein. Products for wide‐ranging applications, including the synthesis of vitamins, were obtained in high yields by precisely controlling principal process parameters. The reactor design permits low organophotocatalyst loadings to generate singlet oxygen. It is anticipated that the efficient aerobic phenol oxygenation to benzoquinones and p ‐quinols contributes to sustainable synthesis. Abstract : The design of a customized continuous‐flow photoreactor enabled a highly efficient aerobic oxygenation of phenols to provide benzoquinones and p ‐quinols. By using pressurized air as oxidant, ecologically benign solvents and low amounts of methylene blue as organophotocatalyst in combination with hyper red LEDs, excellent selectivity values and yields were obtained. The method is expected to improve sustainability for the production of a variety of crucial products and intermediates.